The Implementation Of Text-Based Approach Within The School-Based Curriculum In Senior High School - Ramadhona, Cindy Lutvi; Syaharani, Cinta Nadhifa; Mutmainah, Mutmainah; Hasibuan, Kalayo (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Implementing the text-based approach in school curricula involves incorporating genuine texts into various subjects and teaching activities. This method enhances language learning by encouraging deep interaction with texts and facilitating the contextual teaching of language structures. The research methodology utilized is a literature review, which entails a systematic examination of theories, findings, and pertinent research materials gathered from diverse sources. A literature review includes evaluations, synopses, and the author's interpretations from multiple library sources. This examination focused on content relevant to the research objectives and outcomes. The findings suggest that the text-based approach promotes active engagement with texts, contextual language instruction, and opportunities for developing critical and analytical skills among high school seniors. Challenges include limited teaching resources necessitating investments in diverse texts and materials. The curriculum needs to be adjusted accordingly by integrating texts across subjects and designing analytical tasks.